Systematic literature review using PRISMA: exploring the influence of service quality and perceived value on satisfaction and intention to continue relationship - Budiarto Tedja; Mochammad Al Musadieq; Andriani Kusumawati; Edy Yulianto (Future Business Journal)
Abstract This study aims to develop a systematic review of the influence of Service Quality and Perceived Value on Satisfaction and Intention to Continue the Relationship from an international and empirical perspective. The Preferred Reporting Items for Systematic Reviews and Meta-analyzes (PRISMA) is used as a guideline for systematic literature review to collect data. The selected journal timeframe is from 2008 to 2024, with 22 chosen articles meeting the criteria. Analysis of the selected primary studies reveals that the concepts of Service Quality and Perceived Value can be associated with Satisfaction and Intention to Continue the Relationship. However, an inconsistency was found that there was a significant and insignificant relationship between Perceived Value and Intention to Continue the Relationship, indicating the need for further development to be scientifically verified and to serve as a gap and reference for future researchers to investigate in different research settings. Novelty: Studies related to Intention to Continue the Relationship measured based on Service Quality, Perceived Value, and Satisfaction have been limited. Additionally, this study attempts to develop a more comprehensive concept or model of Intention to Continue the Relationship involving Service Quality, Perceived Value, and Satisfaction.